The Numerical and Experimental Analysis of Concrete Bridges of Different Typologies - Leonel Osvaldo Pico; María Haydeé Peralta; Norma Luján Ercoli; Salvador La Malfa (Revista Cubana de Ingeniería, 2011)
The increase in vehicular load and velocity over the years has prompted the need for structural modifications of concrete bridges. The measurements and analysis of vibrations in «situ» along with numerical techniques aid in the global evaluation of these structures by obtaining the dynamic characteristics and corresponding response. These measurements are then compared to international standards and codes in order to formulate superior concrete bridges with the objective of obtaining the influence of the difference in typology on the behavior of bridges. Bridge 1 uses a two way system with beams and deck slabs and bridge 2 is a superior structure composed of pretension T beams and situ-cast concrete deck. These findings are fundamental references in the designing of bridges.